Development plans in Colombia: Social and economic progress from 1961 to 2022 (2024)
The primary objective of this article is to determine the social and economic advancements achieved in Colombia through the development plans approved and executed between 1961 and 2022. This is a descriptive, longitudinal study with a retrospective design, employing documentary techniques to access information from institutional primary sources and secondary sources necessary for analyzing the regulatory framework regarding planning and the outcomes of the plans approved during the mentioned period. Among the indicators used to ascertain these advancements are data related to coverage in education, health, and public services, the offering of social housing, gross domestic product, per capita income, exports, and imports. The results show that the country achieved significant economic and social progress during these six decades of plan implementation. A key conclusion is that executing each national development plan requires not only financial resources but also greater individual, collective, and regional commitments that can truly contribute to mitigating persistent problems, especially extreme poverty, drug trafficking, labor informality, and violence in rural areas.